Endothelial Damage in JAK2V617F Myeloproliferative Neoplasms with Splanchnic Vein Thrombosis - De Moner, Blanca; Martinez-Sanchez, Julia; Garrote, Marta; Ramos, Alex; Ventosa-Capell, Helena; Moreno-Castaño, Ana; Nomdedeu, Meritxell; Ojeda, Asunción; Escolar, Gines; Garcia-Pagan, Joan Carles; Arellano-Rodrigo, Eduardo; Carreras, Enric; Alvarez-Larran, Alberto; Díaz-Ricart, Maribel (Thrombosis and Haemostasis, 2025)
JAK2V617F-mutated myeloproliferative neoplasms (MPN) exhibit abnormal proliferation of bone marrow progenitors and increased risk of thrombosis, specifically in splanchnic veins (SVT). The contribution of the endothelium to the development of the prothrombotic phenotype was explored.Plasma and serum samples from JAK2V617F MPN patients with (n=26) or without (n=7) thrombotic debut and different treatments, were obtained (n=33). Cultured endothelial cells (ECs) were exposed to serum samples from these patients and from healthy donors as controls. Changes in markers of inflammation (VCAM-1, ICAM-1), cell permeability (VE-cadherin), production of VWF, extracellular matrix (ECM) reactivity, and activation of intracellular signaling pathways related to stress, proliferation, inflammation (Akt, p44/42, IkBa), and JAK2/STAT3 pathway, were assessed by immunofluorescence, flow adhesion, SDS-PAGE and immunoblot. Additionally, circulating markers of endothelial activation and damage (VWF, sVCAM-1, sTNFRI, thrombomodulin, angiopoietin-2, a2-antiplasmin activity, PAI-1) were evaluated in Patients' plasma.The in vitro studies showed that EC exposure to MPN thrombotic patients' sera resulted in increased VCAM-1 and ICAM-1, and reduced VE-cadherin expression (p<0.05) at the cell surface. Production and release of VWF to the ECM were higher (p<0.05), with increased platelet adhesion after perfusing whole blood, being more noticeable in response to sera from non-treated patients. Furthermore, intracellular activation of Akt, p44/42, IkBa and JAK2/STAT3 was observed. Moreover, plasma levels of VWF, TNF-R1, VCAM-1, thrombomodulin, and angiopoietin-2 were higher in JAK2V617F+ MPN patients with thrombosis.The present findings suggest that circulating factors in MPNs with SVT debut induce endothelial proinflammatory and prothrombotic phenotypes, which are modulated in vitro with MPN treatment.
Keywords: endothelial cells; myeloproliferative neoplasms; splanchnic vein thrombosis; JAK2V617F; inflammation